2002
DOI: 10.2337/diacare.25.8.1371
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Insulin Resistance Syndrome in Southwestern France and Its Relationship With Inflammatory and Hemostatic Markers

Abstract: OBJECTIVE -To assess the prevalence and relationships of insulin resistance syndrome (IRS) with inflammatory and hemostatic markers in a representative sample of the population of Southwestern France aged 35-64 years.RESEARCH DESIGN AND METHODS -In this cross-sectional study, data were collected from 597 men and 556 women and were assessed regarding BMI, blood pressure, total and HDL cholesterol levels, triglyceride level, glucose level, plasma insulin level, white blood cell count, fibrinogen level, factor VI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
81
2
7

Year Published

2004
2004
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(97 citation statements)
references
References 31 publications
7
81
2
7
Order By: Relevance
“…Leukocyte count, as a marker of inflammation, may be considered as a component of the metabolic syndrome. The increase in leukocyte count associated with the metabolic syndrome was also found in other studies using NCEP-ATPIII 17,[21][22] or WHO criteria, 23 confirming the link between inflammation and the metabolic syndrome. Ridker et al 26 recently stated that, given the consistency of data on hsCRP in large epidemiological studies, the time has come to add hsCRP as a clinical criterion for the metabolic syndrome.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Leukocyte count, as a marker of inflammation, may be considered as a component of the metabolic syndrome. The increase in leukocyte count associated with the metabolic syndrome was also found in other studies using NCEP-ATPIII 17,[21][22] or WHO criteria, 23 confirming the link between inflammation and the metabolic syndrome. Ridker et al 26 recently stated that, given the consistency of data on hsCRP in large epidemiological studies, the time has come to add hsCRP as a clinical criterion for the metabolic syndrome.…”
Section: Discussionsupporting
confidence: 80%
“…While we did not find higher levels of vWF:Ag in subjects with the metabolic syndrome defined with the NCEP-ATPIII criteria, we did find significantly higher levels of vWF:Ag in patients with the metabolic syndrome using the WHO criteria in the whole group and the female subgroup. Results from other studies are rather conflicting: while two other studies using WHO criteria 23,24 also did not find higher levels of vWF:Ag in subjects with the metabolic syndrome, a recent study in older hypertensive patients 25 did find higher levels of vWF:Ag using both NCEP-ATPIII and WHO criteria. However, in the latter study, 25 Figure 1 Leukocyte count, fibrinogen, von Willebrand factor and plasminogen activator inhibitor-1 (PAI-1) activity in subjects classified according to the number of components of the metabolic syndrome (NCEP-ATPIII criteria).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Some of these abnormalities are linked to insulin resistance, a metabolic disturbance accompanied by an increased acute-phase response. 2 Crosssectional studies [3][4][5] have described metabolic syndrome as a common condition associated with increased CRP levels and prospective evaluations have shown that high CRP levels predict the development of the syndrome. 6 With varying magnitude, individual constituents of metabolic syndrome have been associated with increased CRP levels.…”
Section: Introductionmentioning
confidence: 99%
“…However, the metabolic syndrome, a clustering of cardiovascular risk factors, particularly increased blood pressure and triglycerides [TG] and decreased high density-lip- oprotein cholesterol [HDL-C] along with increasing insulin concentrations, is typically observed in insulin-resistant subjects before the onset of diabetes mellitus [2]. Increased levels of prothrombotic factors, such as PlasminogenActivator-Inhibitor-1 [PAI-1] [3 -6], and inflammatory markers, such as C-Reactive Protein [CRP] [6,7], have also been found to be associated with hyperinsulinaemia or more frequent in subjects with insulin resistance. Hyperinsulinaemia in the context of the metabolic syndrome is supposed to occur as a compensation for insulin resistance.…”
Section: Introductionmentioning
confidence: 99%